Performance Measurement in ITG Based on Balanced Scorecard - Haviluddin Haviluddin; Rayner Alfred (Institute of Advanced Engineering and Science, 2014)
The article reports on our work in conducting performance measurement for the management of Information Technology (IT) by applying the Balanced Scorecard (BSC) at Mulawarman University, Samarinda, East Kalimantan, Indonesia. The results of this study are then used to propose a hybrid framework that applies both BSC and a artificial intelligence (AI) techniques in order to measure the performance of IT governance generally. This article also examines BSC’s abilities and its flexibility compared to other methods in measuring the performance of IT governance. The proposed hybrid framework is expected to yield a management that produces a scorecard measures that are more rigorous, accurate and consistent with the objectives and organizational strategies in non-profit organizations, especially educational ones.